Finite Element Assessment and Fatigue Life Improvement of the Torsion Spring in Hinge - Bayrak, Ramazan; Kenan, Hamit; Coskun, Umut; Guzeltepe, Nurettin (SPRINGERNATURE, 2025)
Fatigue, arising from repetitive loading and unloading cycles, often leads to material failure, typically driven by stress concentrations. This study investigates the fatigue failure analysis of torsion springs used in wooden kitchen furniture hinges, where each hinge contains at least one spring responsible for controlled door movements. The research combines experimental and theoretical approaches, utilizing two distinct experimental setups: one conforming to TS EN 15570:2008 standards for door simulation and another optimized for efficiency. The experimental phase examines various scenarios, including the transition to EN 10270-1 SH material and modifications in spring geometry, such as square cross sections and spiral interval adjustments. A comprehensive finite element model using ANSYS is developed to predict fatigue behavior and validate experimental results. The model successfully identifies critical stress locations, which confirms the actual failure points observed during testing. The study incorporates the Goodman mean stress correction method and considers multiple modifying factors to generate accurate S-N curves for fatigue life prediction. Results demonstrate that while material changes to EN 10270-1 SH showed improved fatigue performance, geometric modifications done in the study primarily altered the location of maximum stress rather than reducing it. The research concludes that accurate finite element modeling at the design stage, combined with experimental validation, is crucial for predicting and optimizing spring fatigue life in practical applications.
Keywords: Fatigue failure; Torsion spring; Finite element assessment; FAILURE ANALYSIS; Engineering